Answer:
Step-by-step explanation:
Using the equation of line
y - y_1 = m(x - x_1)
y = mx + C
First first the slope of the equation
y = 9x - 4
Note: if two lines are perpendicular, their slope will be negative reciprocal
Slope = 9, but because it is perpendicular
m = -1/9
Using the equation
y - y_1 = m(x - x_1)
With the point (-9,-17)
x_1 = -9
y_1 = -17
y - (-17) = -1/9(x - (-9)
y + 17 = -1/9(x + 9)
y = -1/9(x + 9) - 17
Open the bracket.
y = (-x -9)/9 - 17
Lcm is 9
y = -x -9 - 153 / 9
y = -x - 162 / 9
Let's separate
y = -x/9 - 162/9
y = -x/9 - 18
y = -1/9x - 18
Therefore, the equation of the line is y = -1/9x - 18